Pusa Parthenocarpic Cucumber-6: A high-yieldingearly bloomer for protected cultivation - Munshi, D.; Behera, T. K.; Sureja, Amish K.; Singh, Awani K.; Singh, Balraj; Tomar, B. S.; Singh, J. (Indian Horticulture, 2025)
Pusa Parthenocarpic Cucumber-6 is the first extra early (40-45 days for first fruit harvest) improved variety of parthenocarpic gynoecious cucumber suitable for cultivation in protected condition developed by ICAR-IARI for north Indian plains. Apart from superior quality characters, it showed 31.58%, 28.47%, and 21.36% higher yield over the checks (Pant Parthenocarpic Cucumber-2, Aviva and Asma) during winter season (off-season, November-March) under low cost polyhouse.